2006
DOI: 10.1021/jo060667p
|View full text |Cite
|
Sign up to set email alerts
|

The Bogorol Family of Antibiotics:  Template-Based Structure Elucidation and a New Approach to Positioning Enantiomeric Pairs of Amino Acids

Abstract: The sequence positions of d and l Leu and Lys residues in bogorol A (1) have been defined by a simple and novel approach that utilizes small amounts of sample and focuses on detecting the order in which amino acids are liberated from the parent peptide during acid-catalyzed hydrolysis. This technique builds on a previously established relationship between the steric and electronic features of amino acids and their predilection for acidic liberation from polypeptides via dipeptides. The results, which complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
78
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 28 publications
4
78
0
Order By: Relevance
“…The antifungal substances were isolated from the fermentation broth through a procedure involving ammonium sulfate deposition, CM Sepharose Fast Flow chromatography, and reversed-phase HPLC. Structure analysis through FTIR-MS, MS/MS, and 1 H-NMR and 13 C-NMR showed that the main antifungal substance component B is identical to bogorol B described in the literature (Barsby et al 2006). Bogorols A, B, C, D, and E comprise a group of antibacterial peptides isolated from the cells of the marine bacterium Br.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The antifungal substances were isolated from the fermentation broth through a procedure involving ammonium sulfate deposition, CM Sepharose Fast Flow chromatography, and reversed-phase HPLC. Structure analysis through FTIR-MS, MS/MS, and 1 H-NMR and 13 C-NMR showed that the main antifungal substance component B is identical to bogorol B described in the literature (Barsby et al 2006). Bogorols A, B, C, D, and E comprise a group of antibacterial peptides isolated from the cells of the marine bacterium Br.…”
Section: Discussionmentioning
confidence: 72%
“…Bogorols A, B, C, D, and E comprise a group of antibacterial peptides isolated from the cells of the marine bacterium Br. laterosporus PNG-276 (Barsby et al 2001(Barsby et al , 2006. The structures of the bogorol family are based on the same template.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After careful consideration, we concluded that this new compound is a member of a linear cationic antimicrobial lipopeptide family for which scattered information is available in the published litera- (29) reported the isolation of the first known compound in this family from a marine Bacillus sp. The producer organism was later reclassified as B. laterosporus by the same researchers (30). The lipopeptide was named bogorol A and is different from our brevibacillin in two amino acid resides at positions 5 and 9; isoleucine and valine in brevibacillin are replaced by valine and leucine in bogorol A, respectively.…”
Section: Discussionmentioning
confidence: 99%